(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Introduction: Drug utilization Review (DUR) also referred to be as drug utilization evaluation (DUE) and Drug utilization Pattern (DUP). It is defined as ongoing, authorized and systemic quality improvement process. WHO in 1977 defines drug utilization as “The marketing, distribution, prescription and use of drug in a society with special emphasis on resulting medical, social and economic consequences”. Drug utilization studies evaluate drug use at a population level, According to age, sex, social class. They provide feedback on drug utilization data to the prescribers. DUP Involves a comprehensive review of patient’s prescription and medication data before, during, and after dispensing to ensure appropriate medication decisions making and positive patient outcomes. Drug utilization pattern play a significant role in helping the healthcare system to understand, explain and improve the prescribing administration the use of medications. Pharmacokinetic and pharmacodynamics in general department differs in various age groups. The ultimate goal is to achieve rational and effective pharmaceutical care to the general department patients. This has resulted in a clarification of their uses, wider indications, and alternative methods of delivery. DU studies become one of the power full tools in evaluation of health system. Method: we conducted a single cantered observational and prospective analysis in general department patients age between 10-80 years at Sri sai niharika nursing home, old palnadu bus stand, narasaraopet. A total number of 1648 prescriptions were recorded. The drug data such as name of the drug, dosage-form, dosing frequency, route of administration were also noted. The results were presented as percentage. Conclusion: This study provides the information about the prescribing patterns of drug in general department patients. And conclude the role of clinical pharmacist is vital to be an integral part well as to clear the irrational use of drugs in general department. Pharmaceutical care is needed in the correct management of drugs which is even more important in case of general patients. The WHO core indicators helped to improvise the prescribing pattern, identify significant problems involved in the knowledge gap of patients or care takers understanding of instructions provided by consultants and even to minimize the cost burden on the patients.